Nutrient Composition and Antioxidant Properties of Magifera Pajang Kosterm Juice Powder and its Effects on Cardiovascular Biomarkers in Hypercholestrolemic Rabbits and Healthy Human Subjects - Ibrahim, Muhammad (2010)
The main objective of this study was to determine the nutrient composition, antioxidant properties and effects on cardiovascular biomarkers of Mangifera pajang juice powder in hypercholesterolemic rabbits and healthy human subjects. There were three phases in this study. In phase one, the nutritional composition analysis showed that every 100 g of bambangan juice powder (BJP) per wet basis contained 10% moisture, 4% crude protein, 2% crude fat, 76% carbohydrate, 3% ash, 0.8% total dietary fibre (0.1% insoluble and 0.7% soluble dietary fibre), 132 mg ascorbic acid, 36 mg β-carotene and 19 mg gallic acid equivalent (GAE) total phenolics. Ferric reducing/antioxidant power (FRAP) and diphenyl picrylhydrazyl (DPPH) assays showed that BJP had significantly higher (p<0.05) antioxidant capacity by 45 (FRAP value of 40 mM/100 g) and 17% (DPPH value of 52% of radical scavenging activity), respectively as compared to bambangan pulp powder (BP) (FRAP value of 27 mM/100 g; DPPH value of 43% of radical scavenging activity). In phase two, animal experiment was conducted to examine the effects of daily supplementation of BJP at different dosage (5%, 15%, 25% and 35%) on CVD risk biomarkers in hypercholesterolemic rabbits. Supplementation with 25 % of BJP was found to be significantly decreased (p<0.05) the total cholesterol (TC), triglycerides (TG) and low density lipoprotein cholesterol (LDL-C) by 37%, 67% and 30%, respectively. Furthermore, supplementation with 25% of BJP had significantly reduced (p<0.05) the ratio of TC to HDL-C by 25%. Supplementation with 4 different doses of BJP had significantly decreased (p<0.05) plasma malondialdehyde (MDA) by 86%, 89%, 84% and 87%, respectively. Similarly, supplementation with 4 different doses of BJP had significantly (p<0.05) decreased the hepatic MDA contents by 80%, 77%, 77% and 83%, respectively. BJP supplementation had significantly reduced (p<0.05) the percentage of lesion by 23% to 66% as compared to that of positive control (CD) group and more pronounced in the BJP25 group. Supplementation with BJP had significantly increased (p<0.05) the plasma glutathione peroxidase (GPx) and superoxide dismutase (SOD). Similarly, the BJP supplemented groups also showed a significant increment (p<0.05) in hepatic GPx and SOD which ranged between 25% to 62% and 21 to 43%, respectively. Plasma and hepatic GPx and SOD activities had significantly increased in BJP25 and BJP35 groups compared to the other BJP supplemented groups. Supplementation with BJP had significantly increased (p<0.05) hepatic total antioxidant status (TAS) by 16% to 58%. The levels of plasma ascorbic acid were significantly increased (p<0.05) in the BJP25 and BJP35 by 44% and 67%, respectively. Supplementation with 15%, 25%, and 35% of BJP had significantly increased β-carotene by 71%, 78% and 83%. Lower levels of plasma alkaline phosphatase (ALP) and alanine aminotransaminase (ALT) were registered due to the BJP supplementation. In phase three, the effects of BJP on CVD risk biomarkers in normocholesterolemic subjects in a cross-over, single-blind, and placebo-controlled trial were carried out. A total of 100 subjects were screened among staff and postgraduate students of the Faculty of Medicine and Health Sciences (FMHS), Universiti Putra Malaysia (UPM), Malaysia. Ethical approval was obtained from Medical Research Ethics Committee, FMHS, UPM and the subjects were provided informed consent letter to participate in the study carried out at the Nutrition Counseling Laboratory at FMHS, UPM. The study consisted of 32 subjects who were observed over a period of 4 weeks. The subjects ranged from 23 to 28 years old with a cholesterol level of 3.92 to 4.83 mmol/L. Similar to animal findings (Chapter 4), supplementation of 250 ml BJP drink per serving per day led to a significant decrease in TC (18%, p<0.05), ratio of TC:HDL cholesterol (48%, p<0.05) and MDA (23%, p<0.05). However, there were no significant changes for other biomarkers. Compared with placebo, supplementation with BJP increased the concentration of plasma β-carotene (1.62 ± 0.02 vs 2.30 ± 0.05 μmol/L, p<0.05) and ascorbic acid (78.25 ± 5.69 vs 92.43 ± 4.58 μmol/L, p<0.05) significantly at the end of the study by 37% and 22% respectively. TAS tend to be greater after consumption of BJP than placebo and positively related (r=0.92, p<0.001) with plasma ascorbic acid and (r=0.73, p<0.05) with β-carotene. In conclusion, these findings indicated that supplementation of BJP in daily diet may have the potential benefits to provide a protection against cardiovascular disease by lowering the related risk biomarkers and concurrently increasing the antioxidant status in normocholesterolemic subjects. The findings were further supported with the data gathered from animal study where daily supplementation of BJP for 10 weeks had lowered the risk factors for cardiovascular disease evident by the significant correlation (p<0.05) with antioxidant properties present in BJP. Therefore, supplementation with BJP is beneficial as an alternative way to provide effective prevention from cardiovascular disease.